Internalization Of Understanding Of Poor People Reproductive Health (Case Study In Mangasa Village Tamalate Subdistrict In The City Of Makassar) - Nurul Fitri Sugiarti Syam; Ilcham Syarief Kasim (Jurnal Life Birth, 2020)
Lack of public awareness of the importance of education makes many families caught in the vicious cycle of poverty which will ultimately affect the health sector, especially health reproduction. This research aimed to find out the depth information on the Internalisation of Understanding of Poor People Reproduction Health. This study uses a qualitative design with the research type of case study. The informants of this study are key informants (Health Officers), ordinary (the poor people), and the supporters (head of RW, Health Cadre). The data collection was conducted through observation, interview, and documentation. The data were then analyzed by triangulation analysis. The results showed that there is still a lack of knowledge on reproductive health in most of the poor people due to ineffective socialization activities conducted by parties related to the poor is still less so that the acceptance of society's poor reproductive health is still very limited. It is suggested that the increase of knowledge on the poor by regularly counseling on the poor by involving the role of parents, family, a community of peers. All poor people should find information on the health workers and people around them. The health workers further improve program promotion and education through reproductive health education.